"We're not a bottomless pit": food banks' capacity to sustainably meet increasing demand. (31st March 2018) - Iafrati, Steve
Abstract : Based on research with 21 food banks across eight local authority areas in England, this article examines the sustainability of food banks in their attempts to balance demand and supply. Against a background of multiple deprivation and welfare reforms in the UK, food banks are becoming increasingly important for growing numbers of people. However, at a time when food banks' ability to meet this increasing demand is close to capacity, this article examines how social purpose is a core element in food banks' understanding of sustainability. With food banks having little control over the level of demand, and supply being increasingly close to capacity, if demand exceeds supply, sustainability will necessitate either denying demand or expanding supply.